A perspective on complex networks in the stock market - Park, Jihun; Cho, Chang Hee; Lee, Jae Woo (Frontiers in Physics, 2022)
A stock market is a complex system consisting of many interacting agents. We consider recent progress of the complex networks in the stock market constructed by the cross-correlation of the financial time series. We review some methods and discuss about the challenges to generate the reasonable threshold networks in the stock market.